Assistive technology for Para-badminton athletes: the application of the matching person and technology theoretical model in occupational therapy - Soares, L. F. L.; Tormin, L. M.; Carvalho, K. S.; de Jesus Alves, A. C. (Disability and Rehabilitation: Assistive Technology, 2022)
Purpose The objective was to identify the AT demands of para-athletes in para-badminton and present the process of prescription, and follow-up of the AT devices. Also, to evaluate the expectations and the level of satisfaction with the service provided and the AT device.